Risk management in small and medium enterprises: A case study in the Republic of North Macedonia - AMETI, Ilaz; XHEMAILI, Sejdi (Edelweiss Applied Science and Technology, 2026)
Risk management is a global concern for business survival. While large corporations dedicate significant professional and financial resources to this process, small and medium enterprises (SMEs) worldwide are increasingly recognizing the importance of effective risk management. This study, based on statistical data and other research methods, identifies the factors influencing and practices employed in risk management by SMEs in the Republic of North Macedonia. Business and entrepreneurship literature indicate that several factors determine the success and growth of an enterprise. Profitability is one of the most crucial factors for an enterprise's survival in a competitive market environment. Profitability refers to the ability of an enterprise to be financially successful, which can be assessed before entering a business or used to analyze an enterprise that is currently operational. The study also examines the impact of internal and external factors, including the economic environment, access to finance, managerial experience, and organizational strategies, on improving SME performance. The findings aim to contribute to the development of more effective policies and strategic approaches that support the sustainable growth and long-term competitiveness of the SME sector.